2023
DOI: 10.3324/haematol.2022.282399
|View full text |Cite
|
Sign up to set email alerts
|

<i>PARP1</i> and <i>POLD2</i> as prognostic biomarkers for multiple myeloma in autologous stem cell transplant

Abstract: Multiple Myeloma (MM) is an incurable plasma cell malignancy often treated by autologous stem cell transplant (ASCT). Clinical response to ASCT has been associated with DNA repair efficiency. Here we interrogated the role of the base excision DNA repair (BER) pathway in MM response to ASCT. Across 450 clinical samples and six disease stages, expression levels of genes in the BER pathway were found to be highly upregulated during the development of MM. In a separate cohort of 559 patients with MM treated with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 41 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…There are some guidelines with which to evaluate whether patients are suitable for ASCT therapy, such as age, performance status, and comorbidities (especially kidney dysfunction), which are used for short-term risk events. For long-term benefits, there have been some risk factor studies, including lymphocytes after ASCT [ 33 ], expression of PARP1 and POLD2 [ 34 ], very good partial response (VGPR) [ 35 ], minimal residual disease [ 36 , 37 ], and PET/CT scan near day 100 post-ASCT [ 38 ]. These indices, whether before or after ASCT, provide information about ASCT patients’ long-term benefits.…”
Section: Discussionmentioning
confidence: 99%
“…There are some guidelines with which to evaluate whether patients are suitable for ASCT therapy, such as age, performance status, and comorbidities (especially kidney dysfunction), which are used for short-term risk events. For long-term benefits, there have been some risk factor studies, including lymphocytes after ASCT [ 33 ], expression of PARP1 and POLD2 [ 34 ], very good partial response (VGPR) [ 35 ], minimal residual disease [ 36 , 37 ], and PET/CT scan near day 100 post-ASCT [ 38 ]. These indices, whether before or after ASCT, provide information about ASCT patients’ long-term benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Also, researchers found that high expressions of certain BER genes, such as MPG (Nmethylpurine DNA glycosylase) and PARP3 [Poly (ADP-ribose) polymerase 3], are linked to improved overall survival in MM patients who received autologous stem cell transplantation. On the other hand, increased expressions of PARP1 and POLD2 (DNA polymerase delta subunit 2) are associated with worse outcomes in MM, suggesting that targeting BER pathway might improve treatment effectiveness [19][20][21]. Moreover, the gene expression patterns in normal plasma cells and newly diagnosed MM samples reveal that upregulation of the Nucleotide Excision Repair (NER) protein ERCC3 (excision repair cross-complementation group 3) is linked to poorer survival.…”
Section: The Ddr Network In the Onset And Progression Of MMmentioning
confidence: 99%
“…Although discovered in 1974, decades of research have only begun to reveal the broader framework of BER, leaving the specific regulatory network and individual regulatory mechanisms of related proteins largely unresolved [ 13 ]. Key biomolecules participating in the BER pathway include XRCC1 as a repair scaffold [ 14 , 15 ], DNA polymerase β (pol-β), DNA ligase 1, DNA ligase 3, and PARP-1 [ 16 , 17 ]. Among them, PARP-1 plays a pivotal role in the BER pathway.…”
Section: Introductionmentioning
confidence: 99%